2009
DOI: 10.1016/j.jpainsymman.2009.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Disturbances in Patients with Advanced Cancer and Their Family Carers

Abstract: Sleep disturbance is common in patients with advanced cancer, and their family carers also may suffer from sleep problems. The aims of this study were to determine the prevalence of sleep-wake disturbances in patients with advanced cancer and their carers, to monitor the amount of daytime spent in activity and rest, and to examine the relationship between sleep, physical, and psychological symptoms. This was a prospective, descriptive observational study in patients with advanced incurable cancer and their car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
106
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 36 publications
10
106
2
2
Order By: Relevance
“…32 In fact, research has reported that caregivers commonly suffer from sleep problems. 33 However, much sleep research has been focused primarily on the sleep of caregivers of persons with cancer [34][35][36][37][38] and dementia/Alzheimer's disease. 33,[39][40][41] Additionally, it has been shown that short self-reported sleep duration is independently associated with a modest increased risk of coronary events 42 and CHD death.…”
Section: Discussionmentioning
confidence: 99%
“…32 In fact, research has reported that caregivers commonly suffer from sleep problems. 33 However, much sleep research has been focused primarily on the sleep of caregivers of persons with cancer [34][35][36][37][38] and dementia/Alzheimer's disease. 33,[39][40][41] Additionally, it has been shown that short self-reported sleep duration is independently associated with a modest increased risk of coronary events 42 and CHD death.…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, this phenomenon of poor sleep is not limited to cancer patients, but also affects their caregivers. 5 Sleep disturbance is associated with a number of negative consequences that, when combined, affect the health-related quality of life (QOL) in an individual. 6 A disruption in the regular sleep schedule can interfere with the restorative function of sleep, thereby drastically decreasing the QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Kanser tanısı almış ço-cukların ebeveynlerinin fiziksel psikolojik ve sosyal iyilik hallerinin incelendiği başka bir çalışmada da bakım veren ebeveynlerin uyku bozukluklarının yüksek oranda olduğu ve çocuklarının bakımı ve kanserle ilgili yaşadıkları endişe nedeniyle daha az uyudukları, uykuya dalmakta zorlandıkları ve uykuyu devam ettirmede sıkıntı yaşadıkları belirtilmiştir. [24] Ayrıca Gibbins ve ark.nın [25] çalışmasında (2009) …”
Section: Discussionunclassified